Factors associated with anxiety and depressive symptoms among Indonesian adolescents during the COVID-19 pandemic: a cross-sectional study - Rika Sarfika; I Made Moh. Yanuar Saifudin; Hema Malini; Dewi Eka Putri; Anggi Lukman Wicaksana; Mahathir Mahathir; Dwi Novrianda (PAGEPress Publications, 2023)
Despite the conclusion of the pandemic, addressing mental health concerns during disasters remains crucial. Examining the impact of mental health issues in such contexts yields valuable insights for preventing future crises. This study aimed to examine the factors linked to anxiety and depression symptoms among Indonesian adolescents during the COVID-19 pandemic. This was a cross-sectional study. The study utilized an online survey collected from 738 participants from 34 provinces in Indonesia. The participants were asked to provide information on their demographics, social media exposure, self-rated health, GAD-7 scores, and the WHO-5 well-being index. The associations between participant characteristics and depression and anxiety were investigated using independent t-tests, ANOVA tests, and ordinal logistic regression. The majority of the participants were late adolescents, aged 18-21 years old (95%), and female (79.1%). Factors such as gender, self-rated health, and social media exposure were significantly associated with depression and anxiety among adolescents during the COVID-19 pandemic. Male adolescents had a higher risk of depression (OR=0.657, 95% CI=0.476-0.908), while infrequent social media exposure was linked to lower anxiety levels (OR=0.401, 95% CI=0.190-0.847). The study revealed that younger age, female sex, suspected COVID-19 infection, and excessive social media exposure were associated with higher levels of depression and anxiety. To manage depression and anxiety during and after pandemics, it is crucial to provide valid and reliable information and healthcare services, foster social connections, and create supportive environments in households and workplaces.